Chronic spontaneous urticaria in adult patients : evaluating the effect of loratadine on weight and metabolic syndrome - Heah, Swee Kuan; Adawiyah Jamil,; Mohan Arumugam,; Tang Min Moon,; Norlaila Mustafa, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Antihistamine is standard chronic spontaneous urticaria (CSU) therapy. Weight gain is a side effect of concern as prolonged high dose therapy is common. We investigated the effects of 12-weeks loratadine therapy on weight, appetite and parameters of metabolic syndrome (MetS). A cohort study was performed involving CSU patients aged ≥18 years. Patients with diseases or on drugs affecting weight or appetite were excluded. CSU was treated according to standard management. Weight, height, waist circumference (WC), body mass index (BMI) and blood pressure (BP), Urticaria Activity Score 7 (UAS7), Dermatology Life Quality Index (DLQI), hunger and satiety questionnaire, fasting blood sugar (FBS) and fasting lipid profile (FLP) were obtained at baseline, week 6 and week 12. Loratadine cumulative dose were determined. Thirteen (33.33 %) males and 26 (66.67 %) females aged 33.00 (12.00) years participated. Median weight was 62.55 (18.30) kg, BMI 24.60 (6.80) kg/m2, 13(33.33%) patients had normal weight, 12 (30.77%) overweight, 11 (28.21%) obese and 3 (7.69%) underweight. Significant weight gain was observed at week 6, 67.56 ± 16.14 kg vs 68.16 ± 16.95 kg, p < 0.05 and 67.56 ± 16.14 kg vs 64.73 ± 14.60 kg, p = 0.04 at week 12. Changes in BMI, WC, BP, FBS and FLP were insignificant. Three patients developed MetS. Hunger and satiety scores were unaffected. Loratadine induced weight gain despite no effects on appetite. Weight should be monitored in patients on long term loratadine therapy.